1975
DOI: 10.2307/1128563
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Processing and Cognitive Styles in Learning-Disabled and Normal Children

Abstract: A paradigm of specialized brain hemisphere processing abilities was used to test cognitive skills and cognitive style in "learning-disabled" (LD) and "normal" children. Results indicate that (1) verbal ability is not a unitary factor, and LD children are deficient in only some aspects of verbal ability; (2) the LD group perform as well as the control group on right-hemisphere tests; (3) LD boys are more field sensitive (field dependent) than the control boys; (4) LD children may be attempting to use a nonverba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 31 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Previous studies have suggested a relationship between learning disabilities and field dependence (Guyer and Friedman, 1975); subjects who are field dependent should find it more difficult to locate information embedded within a field of extraneous information and so perform less well on the embedded figures task. Field dependence has also been associated with less focused, more diffuse attention (see Guyer and Friedman, 1975), itself linked to increased creativity (Tarver, Ellsworth and Rounds, 1980). Both field dependence and poor attentional focusing have also been linked to right hemisphere functioning (see Guyer and Friedman, 1975;Shaw and Brown, 1990).…”
Section: Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have suggested a relationship between learning disabilities and field dependence (Guyer and Friedman, 1975); subjects who are field dependent should find it more difficult to locate information embedded within a field of extraneous information and so perform less well on the embedded figures task. Field dependence has also been associated with less focused, more diffuse attention (see Guyer and Friedman, 1975), itself linked to increased creativity (Tarver, Ellsworth and Rounds, 1980). Both field dependence and poor attentional focusing have also been linked to right hemisphere functioning (see Guyer and Friedman, 1975;Shaw and Brown, 1990).…”
Section: Studymentioning
confidence: 98%
“…Field dependence has also been associated with less focused, more diffuse attention (see Guyer and Friedman, 1975), itself linked to increased creativity (Tarver, Ellsworth and Rounds, 1980). Both field dependence and poor attentional focusing have also been linked to right hemisphere functioning (see Guyer and Friedman, 1975;Shaw and Brown, 1990). Thus relationships between creativity, field dependence and dyslexia would be predicted by a right-hemisphere enhancement explanation of the dyslexic's increased creativity.…”
Section: Studymentioning
confidence: 99%
“…The extraction of meaning from some syntactic devices would seem to require that strings of words be retained, in their original order, in short-term or working memory. On the other hand, some of the traditional measures of working memory are unconelated with reading achievement (e.g., Guyer and Friedman, 1975;Hunt et al, 1973Hunt et al, ,1975Perfetti and Goldman, 1976;Waters and Doehring, 1990), and Daneman (1987) has suggested that poorer readers may have an impaired reading-specific, functional working memory, rather than any general working memory deficit. There is, on the other hand, much evidence to suggest that phonological storage provides the best medium for the retention of strings of words (e.g., Baddeley, 1979;Conrad, 1979;Jorm, 1983).…”
Section: Hypothesesmentioning
confidence: 99%
“…As with Downloaded by [University of Calgary] at 16:28 04 February 2015 previous studies, these relationships were in favor of the field independent students. In another study involving boys Guyer and Friedman (1975) compared learning disabled and normal boys, ages 8 to 13, on a variety of measures. The L.D.…”
Section: Fd/i and Overall Reading Performancementioning
confidence: 99%